Arf family GTPases: roles in membrane traffic and microtubule dynamics. (26th October 2005) - Kahn, R.A.; Volpicelli-Daley, L.; Bowzard, B.; Shrivastava-Ranjan, P.; Li, Y.; Zhou, C.; Cunningham, L.
Abstract : Database mining and phylogenetic analysis of the Arf (ADP-ribosylation factor) superfamily revealed the presence in mammals of at least 22 members, including the six Arfs, two Sars and 14 Arl (Arf-like) proteins. At least six Arf family members were found in very early eukaryotes, including orthologues of Arf, Sar, Arl2, Arl3, Arl6 and Arl8. While roles for Arfs in membrane traffic are well known, those for most of the Arls remain unknown. Depletion in cells of the most closely related human Arf proteins, Arf1–Arf5, reveals specificities among their cellular roles and suggests that they may function in pairs at different steps in endocytic and secretory membrane traffic. In addition, recent results from a number of laboratories suggest that several of the Arl proteins may be involved in different aspects of microtubule-dependent functions. Thus, a second major role for Arf family GTPases, that of regulating microtubules, is emerging. Because membrane traffic is often dependent upon movement of vesicles along microtubules this raises the possibility that these two fundamental functions of Arf family members, regulation of vesicle traffic and microtubule dynamics, diverged from one function of Arfs in the earliest cells that has continued to branch and allow additional levels of regulation.